2018
DOI: 10.3382/ps/pey166
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different dietary alterations in their ability to mitigate the incidence and severity of woody breast and white striping in commercial male broilers

Abstract: The following study was conducted to define how multiple nutritional strategies affect broiler performance, meat yield, and the presence and severity of white striping (WS) and woody breast (WB) in high-yielding broilers. Relative to a commercial set of reference broiler diets (Commercial reference diet; Trt 1) that were fed in a 4-phase program, the following nutritional strategies were investigated: increasing the ratio of digestible arginine: digestible lysine (dArg: dLys ranged from 113 to 126; Trt 2), sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 35 publications
3
26
1
4
Order By: Relevance
“…It has been previously reported that the administration of diets with an Arg:Lys ratio of 0.95 and 1.25 exerted no significant effect on the occurrence of WS and WB in 53-day-old broilers [ 49 ]. Bodle et al [ 17 ] recently reported that increasing the digestible Arg:Lys ratio from approximately 111–113% to 120–125% reduced the severity of WB while had no effects on WS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously reported that the administration of diets with an Arg:Lys ratio of 0.95 and 1.25 exerted no significant effect on the occurrence of WS and WB in 53-day-old broilers [ 49 ]. Bodle et al [ 17 ] recently reported that increasing the digestible Arg:Lys ratio from approximately 111–113% to 120–125% reduced the severity of WB while had no effects on WS.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide has shown marked vasodilator properties [ 9 ] and it could enhance blood flow to the breast muscle alleviating the hypoxic condition usually observed in breasts affected by severe woody breast (WB) or white striping (WS) myopathies [ 15 , 16 ]. Very recently, Bodle et al [ 17 ] showed that WB, but not WS, average score was significantly reduced by increasing the level of dietary arginine.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a slight reduction of moderate cases of WB has been obtained by dietary supplementation of guanidinoacetic acid used a precursor of creatine, but strong interaction with diet composition was found (Cordoba‐Noboa et al., ,b). Recently, it was demonstrated that an increase of arginine:lysine ratio can have a mitigation effect on breast meat abnormalities (Zampiga, Soglia, Petracci, Meluzzi, & Sirri, ) though a similar study led to a divergent outcome (Bodle et al., ). Therefore, until now it seems that there is lack of practical nutrition and management interventions to reduce growth‐related abnormalities in the broiler industry without negatively affecting live and slaughter performances.…”
Section: Means Of Alleviation: Facts and Challengesmentioning
confidence: 99%
“…Previous studies have shown that BW decreases and FCR increases during early protein dilution and feed restriction. However, these can be recovered by day 44 to 49 in various strains of broilers ( Rezaei and Hajati, 2010 , Bodle et al., 2018 ). Nevertheless, an excessive reduction in dietary AA may impact internal organ development and decrease meat deposition ( Zhan et al., 2006 ).…”
Section: Introductionmentioning
confidence: 99%